GEOQUÍMICA DE ELEMENTOS-TRAÇO EM SÓLIDOS EM SUSPENSÃO NO ALTO RIO MADEIRA, RONDÔNIA, BRASIL - Gomes, J. P. O.; Nascimento, E. L.; Bernardi, J. V. E.; Bastos, W. R.; Lacerda, L. D. (Geochimica Brasiliensis, 2012)